Science and Technology Librarians: User Engagement and Outreach Activities in the Area of Scholarly Communication. - Lutishoor Salisbury; Julie Speer (Issues in Science and Technology Librarianship)
This paper highlights the findings of a survey completed by ACRL/STS members on scholarly communication issues. In particular it identifies the percentage of their daily activities that are spent in support of scholarly communication activities; extent of change of job responsibilities in the last five years; roles engaged in relating to scholarly communication including those that are formal responsibilities, those they are informally engaged in, or those with which they have no engagement. It highlights areas in the area of scholarly communication that STS members need to know more about or want to know more about. It presents the status of open access policies at members' institutions and the needs expressed by members about activities that STS or ACRL could undertake to help advance their work in the areas of scholarly communication. [ABSTRACT FROM AUTHOR]